1993
DOI: 10.1136/jnnp.56.11.1164
|View full text |Cite
|
Sign up to set email alerts
|

Anti-sulphatide antibodies in peripheral neuropathy.

Abstract: A study was carried out on 135 patients with chronic idiopathic neuropathy (63), neuropathy associated with monoclonal gammopathy (51, including eight with anti-MAG antibody activity) and the Guillain-Barre syndrome (GBS) (21). Serum IgM, IgG and IgA anti-sulphatide antibody titres were compared with titres in 304 patients with other neurological or immunological diseases and in 50 normal subjects. Titres were presented a) as the highest serum dilution at which reactivity could be detected, and b) in the linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 13 publications
4
33
0
Order By: Relevance
“…It is therefore likely that anti-sulfatide IgM antibodies binding to sensory axons and dorsal root ganglia produce a sensory axonal nerve lesion, whereas in patients with demyelinating neuropathy these antibodies may be directed against sulfatide in the myelin. Morphological studies showed wide myelin lamellae and deposits of IgM on myelin sheets [2,21].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that anti-sulfatide IgM antibodies binding to sensory axons and dorsal root ganglia produce a sensory axonal nerve lesion, whereas in patients with demyelinating neuropathy these antibodies may be directed against sulfatide in the myelin. Morphological studies showed wide myelin lamellae and deposits of IgM on myelin sheets [2,21].…”
Section: Discussionmentioning
confidence: 99%
“…Both axonal and demyelinating neuropathies have been described. 19,30,109 The antibodies are most often polyclonal but also occur as IgM monoclonal gammopathies, except in the small-fiber neuropathies, in which they are invariably polyclonal. 19 Some antisulfatide antibodies crossreact with MAG, P0, or chondroitin sulfate A or C. 19 Passive transfer of antisulfatide antibodies into rabbits or immunization of guinea pigs with sulfatide results in experimental neuropathy.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Similarly, we found no elevated reactivity to sulphatide, although this has also been a target of antibody in neuropathy. 41 CIDP patients had increased T cell reactivity to the gangliosides GM1, GM3, GD3 and possibly GQ1b more frequently than healthy controls and ON patients but the differences were not statistically significant. The proportions of CIDP patients with increased T cell reactivity to gangliosides may be an underestimate, as it is possible that the level of this reactivity may fluctuate with the disease course of CIDP, as we have demonstrated for T cell reactivity to myelin antigens in multiple sclerosis.…”
Section: Discussionmentioning
confidence: 88%